2006
DOI: 10.1016/j.jcrs.2006.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical findings of tamsulosin-associated intraoperative floppy-iris syndrome

Abstract: The prevalence of tamsulosin intake was lower in this study's English population than that reported in the U.S. literature. The duration of tamsulosin intake did not appear to correlate with the severity of IFIS, and the overall complication rate was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 5 publications
3
46
0
5
Order By: Relevance
“…Although IFIS may have a multifactor etiology, systemic treatment with an a 1 -ARA seems to play a pivotal role. 11,12 The association between tamsulosin and IFIS has been confirmed in numerous studies, 5,[13][14][15] as has the fact that IFIS may occur in patients taking other a 1 -ARAs. 11,13,[16][17][18][19][20] In the 2008 American Society of Cataract and Refractive Surgery (ASCRS) IFIS survey, 21 95% of experienced surgeons reported that systemic treatment with the a 1 -ARA tamsulosin makes cataract surgery more difficult and leads to higher rates of complications.…”
Section: J Cataract Refract Surg 2011; 37:1447-1454 Q 2011 Ascrs and mentioning
confidence: 82%
“…Although IFIS may have a multifactor etiology, systemic treatment with an a 1 -ARA seems to play a pivotal role. 11,12 The association between tamsulosin and IFIS has been confirmed in numerous studies, 5,[13][14][15] as has the fact that IFIS may occur in patients taking other a 1 -ARAs. 11,13,[16][17][18][19][20] In the 2008 American Society of Cataract and Refractive Surgery (ASCRS) IFIS survey, 21 95% of experienced surgeons reported that systemic treatment with the a 1 -ARA tamsulosin makes cataract surgery more difficult and leads to higher rates of complications.…”
Section: J Cataract Refract Surg 2011; 37:1447-1454 Q 2011 Ascrs and mentioning
confidence: 82%
“…1 The syndrome is characterized by 3 intraoperative features: a flaccid iris stroma that undulates and billows in response to the intraocular fluid current, a propensity for the floppy iris stroma to prolapse toward the sites of phacoemulsification and side-port incisions despite proper wound construction, and progressive intraoperative pupil constriction despite standard preventive preoperative pharmacologic measures. 1,2 Because such symptoms have often been seen in patients under treatment with a 1 -blockers to improve urination in prostatic hyperplasia, their cause has been found to be associated with a 1 -adrenergic antagonists. [1][2][3][4] Tamsulosin has a long half-life, and a relatively constant receptor blockade could result in a form of disuse atrophy of the iris dilator smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because such symptoms have often been seen in patients under treatment with a 1 -blockers to improve urination in prostatic hyperplasia, their cause has been found to be associated with a 1 -adrenergic antagonists. [1][2][3][4] Tamsulosin has a long half-life, and a relatively constant receptor blockade could result in a form of disuse atrophy of the iris dilator smooth muscle. This might explain not only the poor pupil dilation in patients receiving tamsulosin but also the flaccid and floppy iris stroma observed even after the medication is stopped.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies have found occurrence of IFIS in patients started on tamsulosin for 9 months to 3 years. 3 A minimum duration of 3 months was noted in one study. 3 We report a case of probable IFIS following a minimum of 2 days intake of tamsulosin.…”
mentioning
confidence: 90%